Ultra-small open access microcavities for enhancement of the light-matter interaction - Dolan, P (2012)
The design, construction and characterisation of a novel, arrayed, open-access optical microcavity is described. Included in this thesis are the precise fabrication details, making use of the focused ion beam. A technique for analysing and optimising the microcavities constructed, making use of an atomic force microscope is also included. Results from the optical characterisation of the fabricated microcavities are presented, including quality factors of around 104, and fitnesses of around 400. The optical analysis then progressed onto coupling colloidal semiconductor nanocrystals to the microcavity modes. This yielded room temperature Purcell enhancements, single particle sensing, and also allowed for the characterisation of a second iteration of cavities. This improved set was shown to achieve fitnesses in excess of 1800 and quality factors with a lower limit of 15000. The optical identification of single NV centres in nanodiamond is discussed, along with the development of an optical apparatus to couple them to microcavities at cryogenic temperatures. Finally several results from finite difference time domain simulations will be presented, showing ultimate mode volumes of less than 0.5 cubic wavelengths are possible for this approach.